Genetic diversity analysis using morphological and biochemical traits in baby corn (Zea mays) - RASHMI, KUMARI; RANI, J; SAHAY, SANJAY; MANDAL, S S; SINGH, BIRENDRA; SINHA, SWETA (The Indian Journal of Agricultural Sciences, 2021)
The present investigation was conducted to examine the genetic diversity existing among 24 genotypes of babycorn (Zea mays L.). The experiment was conducted in three replications in randomized block design during rabi 2018-19 at research farm of Bihar Agricultural University, Sabour. Different morphological and biochemical observations were taken to identify diverse genotypes among them. Observations were taken for 10 morphological characters and nine biochemical traits. Analysis of variance showed significant variation in genotypes for all the traits. On the basis of mean performance genotypes Suwan and VQL1 were found to be the best genotypes for baby corn yield. Genotypes LM14 (203.44 q/ha), LM13 (208.73 q/ha), VQL1 (203.25 q/ha), 95IOWA (200.34 q/ha) and Suwan (230.11 q/ha) were found to be the best genotypes for fodder yield. On the basis of D2 Mahalanobis statistical analysis, all the genotypes were grouped into seven clusters. Seven genotypes were found in the cluster III, followed by six genotypes in cluster II and minimum number of genotype was in cluster VI and VII (with one genotype in each cluster). The maximum intra cluster distance was found in cluster V (117.93) followed by cluster III (93.49) and minimum in cluster I (27.64). The maximum inter cluster distance was found in between cluster IV and VII (317.11) and minimum in between cluster I and VII (92.78). The present investigation revealed that cluster IV and VII were most diverse. Genotypes constituted in these clusters may be used as parents for future hybridization.